Exploring the bush yam (Dioscorea praehensilis benth) as a source of agronomic and quality trait genes in white guinea yam (dioscorea rotundata poir) breeding - Adewumi, A.S.; Agre, A.P.; Asare, P.A.; Adu, M.O.; Taah, K.J.; Mondo, J.; Akaba, S. (MDPI, 2022)
Yam (Dioscorea spp.) is an important food security crop in the tropics and subtropics. However, it is characterized by a narrow genetic base within cultivated and breeding lines for tuber yield, disease resistance, and postharvest traits, which hinders the yam breeding progress. Identification of new sources of desirable genes for these traits from primary and secondary gene pools is essential for this crop improvement. This study aimed at identifying potential sources of genes for yield and quality traits in a panel of 162 accessions of D. praehensilis, a semi-domesticated yam species, for improving the major yam species, D. rotundata. Significant differences were observed for assessed traits (p < 0.05), with D. praehensilis genotypes out-performing the best D. rotundata landraces for tuber yield (23.47 t ha−1), yam mosaic virus (YMV) resistance (AUDPC = 147.45), plant vigour (2.43) and tuber size (2.73). The study revealed significant genotypic (GCV) and phenotypic (PCV) coefficients of variance for tuber yield, YMV severity score, and tuber flesh oxidation. We had also a medium-to-high broad-sense heritability (H2b) for most of the traits except for the dry matter content and tuber flesh oxidation. This study identified some promising D. praehensilis genotypes for traits such as high yield potential (WNDpr76, CDpr28, CDPr7, EDpr14, and WNDpr63), resistance to YMV (WNDpr76, CDpr7, EDpr14, CDpr28, and EDpr13), high dry matter content (WNDpr76, CDpr28, and WNDpr24), low tuber flesh oxidation (WNDpr76, CDpr5, WNDpr31, CDpr40, and WNDpr94) and high number of tubers per plant (WNDpr76, CDpr7, CDpr68, CDpr29, and CDpr58). These genotypes could, therefore, be employed in breeding programmes to improve the white Guinea yam by broadening its genetic base.